2008
DOI: 10.1097/mbc.0b013e3283049650
|View full text |Cite
|
Sign up to set email alerts
|

Association of platelet-derived growth factor-D gene polymorphism with ischemic stroke in a Chinese case–control study

Abstract: Stroke is a multiple genetic disease. Platelet-derived growth factor-D has been found to be involved in the pathogenesis of atherosclerosis, suggesting possible association between platelet-derived growth factor-D and the development of ischemic stroke. However, little information on the relationship between platelet-derived growth factor-D and stroke is currently available. The aim of this study was to investigate the association between platelet-derived growth factor-D genetic variation and the risk of ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, the associations of PDGFD variants with other type of stroke, especially ICH have not been investigated [18]. In the present study, we found that the -858A/C variation in the PDGFD promoter region could lead to an enhancement of PDGFD promoter activity and consequently up-regulation of the expression of the gene.…”
Section: Discussionmentioning
confidence: 46%
“…However, the associations of PDGFD variants with other type of stroke, especially ICH have not been investigated [18]. In the present study, we found that the -858A/C variation in the PDGFD promoter region could lead to an enhancement of PDGFD promoter activity and consequently up-regulation of the expression of the gene.…”
Section: Discussionmentioning
confidence: 46%
“…A PDGFD transgenic mouse study showed that PDGFD could induce blood vessel maturation during angiogenesis (42). More importantly, a case-control study demonstrated an association between PDGFD gene polymorphisms and ischemic stroke (43). Heparin-binding EGF-like growth factor (HBEGF), a hypoxia-inducible neuroprotective protein, was reported to play a neuroprotective role by stimulating the proliferation of neuronal precursor cells during ischemia and reperfusion injury (44).…”
Section: Discussionmentioning
confidence: 99%